Pengaruh Konsumsi Rumah Tangga, Angkatan Kerja dan Pengeluaran Pemerintah Terhadap PDRB Jawa Timur: ( THE INFLUENCE OF HOUSEHOLD CONSUMPTION, LABOR FORCE AND GOVERNMENT EXPENDITURE ON EAST JAVA'S GRDP ) - Efendi, Muhammad Rizal; Rachmawati, Lucky (Universitas Negeri Surabaya, 2024)
GRDP which functions as the direction of economic policy in a region. This research was carried out to reveal the impact of Household Consumption, Labor Force and Government Expenditure on Gross Regional Domestic Product in East Java Province during the period 2010-2023. The data analysis approach uses a time series with multiple linear regression. The results of the analysis showed that Household Consumption and Government Expenditure had a significant positive effect on GRDP in East Java Province, while the labor force had a negative and insignificant effect on GRDP in East Java Province.